D614G reshapes allosteric networks and opening mechanisms of SARS-CoV-2 spikes - Fiona L. Kearns; Anthony T. Bogetti; Carla Calvó-Tusell; Mac Kevin E. Braza; Lorenzo Casalino; Amanda J. Gramm; Sean Braet; Mia A. Rosenfeld; Harinda Rajapaksha; Bryan Barker; Ganesh Anand; Lillian T. Chong; et al. (Proceedings of the National Academy of Sciences, 2026)
The severe acute respiratory syndrome coronavirus 2 spike glycoprotein enables infection through a key conformational transition that exposes its receptor binding domain (RBD). Experimental evidence indicates that spike mutations, particularly the early D614G variant, alter the rate of this conformational shift, potentially increasing viral infectivity. We conducted extensive weighted ensemble simulations of the Ancestral, Delta, and Omicron BA.1 spike strains to investigate relationships between sequence mutations and RBD opening dynamics. We observe that Ancestral, Delta, and Omicron BA.1 spike RBDs open differently. Via dynamical network analysis, we identified two allosteric communication networks connecting all S1 domains: the established N2R linker and a newly investigated antiparallel R2N linker. In Delta and Omicron BA.1 variant spikes, RBD opening is facilitated by both linkers, while the Ancestral strain relies predominantly on the N2R linker. In the Ancestral spike, the D614-K854 salt bridge impedes allosteric communication through the R2N linker, whereas the loss of this salt bridge in all subsequent variants of concerns allows for increased local flexibility, thereby accelerating RBD opening. Hydrogen–deuterium mass spectrometry experiments validate these altered dynamics in the D614 region. This study unveils a “hidden” network, connecting the N-terminal domain to the RBD via the 614-proximal region, and the D614G mutation reshapes the fitness landscape of these critical viral glycoproteins.